2019
DOI: 10.1002/wer.1246
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology mediated optimization of Indanthrene Blue RS by a novel isolated bacterial strain Bacillus flexus TS8

Abstract: The enhanced decolorization and detoxification of Indanthrene Blue RS dye, under aerobic conditions, by a novel isolated anthraquinone‐degrading bacterium, Bacillus flexus TS8, has been presented in this paper. The optimal decolorization conditions were determined by response surface methodology based on Box–Behnken design. The results indicated that the strain TS8 possessed the highest decolorization efficacy at pH 10.26, temperature 30.97 ºC and an inoculum size of 10.48% (v/v). It also revealed that about 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The degradation kinetic model for strain A11 was also fitted, from which we obtained 200 mg·L –1 as a watershed for the specific degradation rate, where substrate concentrations greater or less than this value showed varying performance (Figure ). This phenomenon has also been manifested in dye decolorization, where microbial growth was inhibited by the dye concentration . Similar observations indicated that the ability of strain A11 to degrade acephate increased at low acephate concentrations but decreased at higher acephate concentrations.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The degradation kinetic model for strain A11 was also fitted, from which we obtained 200 mg·L –1 as a watershed for the specific degradation rate, where substrate concentrations greater or less than this value showed varying performance (Figure ). This phenomenon has also been manifested in dye decolorization, where microbial growth was inhibited by the dye concentration . Similar observations indicated that the ability of strain A11 to degrade acephate increased at low acephate concentrations but decreased at higher acephate concentrations.…”
Section: Discussionsupporting
confidence: 57%
“…This phenomenon has also been manifested in dye decolorization, where microbial growth was inhibited by the dye concentration. 45 Similar observations indicated that the ability of strain A11 to degrade acephate increased at low acephate concentrations but decreased at higher acephate concentrations. This result may be attributed to the toxicity of acephate to the assayed strain.…”
Section: Discussionmentioning
confidence: 59%
“…It is essential for the survival of all living species and covers 70% of the Earth's surface with only 2% of freshwater (Chamhuri & Ferdoushi, 2014). Although dyes are among the most dangerous pollutants, they are used in many industries such as food, cosmetics, medical, and textile as well as packaging printing (Katheresan, Kansedo, & Lau, 2018;Mohanty & Kumar, 2019). Color prevents light penetration, slows down photosynthesis activity, inhibits the growth of biota, and also has a tendency to chelate metal ions, which results in microtoxicity of fish and other organisms (Garg, Amita, Kumar, & Gupta, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…CCD, a variation of factorial design with repeated central points to estimate the pure error, is a type of experimental design that involves varying the factors at three levels: low, medium and high. CCD provides more efficient estimates of the response surface than factorial designs, especially in the near-optimal region (Mohanty & Kumar, 2020).…”
Section: Introductionmentioning
confidence: 99%